LIFE INSURANCE IN POSITIVE LAW AND ISLAMIC LAW IN INDONESIA - Lubis, Ramiah (Nurani: jurnal kajian syari'ah dan masyarakat, 2020)
Life insurance is an agreement made by an insurance company to its customers that if the customer experiences a risk of death in his life whether in the form of an accident or due to illness, then the insurance company will provide compensation with a certain amount of money in accordance with the premiums paid for being a customer of the insurance company to heirs of the customer. Conventional Insurance and Syariah Insurance are both tasked to manage and cope with risk, it's just that in Syariah Insurance the management concept is carried out using a pattern of mutual risk between managers and participants (risk sharing) or called at takaful and at tadhamun. While in conventional insurance the work pattern is to transfer risk from the customer (participant) to the company (manager), which is called risk transfer. So that the risks regarding the participants will be fully borne by the manager.